Investigating the Dimensionality and Stability of Union Commitment Profiles over a 10-Year Period: A Latent Transition Analysis. (January 2021) - Morin, Alexandre J. S.; Gallagher, Daniel G.; Meyer, John P.; Litalien, David; Clark, Paul F.
The authors adopt a person-centered approach to the investigation of the dimensionality of the union commitment construct by capitalizing on a 10-year longitudinal study (from 1992 to 2002) of 637 union members in their first year of employment measured again 1 and 10 years later. Results reveal four distinct profiles of union commitment, presenting a stable structure over time. These profiles demonstrate consistency in commitment level across the three most common union commitment dimensions, thus questioning the necessity of adopting a multidimensional approach. Results show that union members became more similar to other members of their profiles over time, and that their union commitment became slightly less extreme as union tenure increased. Finally, results show that union commitment profiles predict union participation, in accordance with our expectations, and suggest that endorsing positive attitudes toward unions and their instrumentality was a stronger predictor of profile membership than was satisfaction with the actions of one's own union.